2021
DOI: 10.3389/fneur.2021.738530
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Differentially Expressed MicroRNAs in Saliva of Parkinson's Disease Patients

Abstract: Objective: This study aims to identify differentially expressed salivary miRNAs and validate the diagnostic potential for idiopathic Parkinson's disease (PD). Also, the disease specificity of candidate miRNAs was evaluated between PD, multiple system atrophy (MSA), and essential tremor (ET).Methods: We collected salivary samples from 50 PD, 20 ET, and 20 MSA patients, as well as 30 healthy controls (HCs). In the discovery phase, salivary miRNA microarray analysis was performed. In-silico analysis was used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…Recent studies indicated that salivary microRNAs could serve as potential biomarkers in the diagnosis of PD. 15,16 Apart from noncoding RNA, salivary oligomeric α-syn also showed high potential in the diagnosis of PD. 9,17 Remarkably, the oligomeric α-syn levels and the oligomeric α-syn/total α-syn ratio were increased significantly in the extracellular vesicles of patients with PD compared with healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated that salivary microRNAs could serve as potential biomarkers in the diagnosis of PD. 15,16 Apart from noncoding RNA, salivary oligomeric α-syn also showed high potential in the diagnosis of PD. 9,17 Remarkably, the oligomeric α-syn levels and the oligomeric α-syn/total α-syn ratio were increased significantly in the extracellular vesicles of patients with PD compared with healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Some achievements have been made in the studies of saliva as a noninvasive and easily accessible biospecimen in PD biomarker discovery. Recent studies indicated that salivary microRNAs could serve as potential biomarkers in the diagnosis of PD 15,16 . Apart from noncoding RNA, salivary oligomeric α‐syn also showed high potential in the diagnosis of PD 9,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the different profiles, only one miRNA, miR-324-3p, is commonly downregulated in the brain, body fluids, and EVs of AD patients, but its expression is not altered in AD mouse models. MiRNA profiles have been also characterized in brain [ 126 , 127 , 128 , 129 ], gut [ 130 ], blood [ 128 ], plasma [ 131 , 132 ], serum [ 133 ], CSF [ 134 , 135 ], saliva [ 136 ], and EVs [ 131 , 137 ] of PD patients; in brain of a PD mouse model [ 135 ]; in blood of a PD rat model [ 138 ]; and in a PD in vitro model [ 139 ]. Although no common miRNAs are found when comparing all the above-mentioned PD profiles, there are common miRNAs between some tissues and body fluids.…”
Section: Epigenetic Changes In Prion-like Diseasesmentioning
confidence: 99%
“…The following supporting information can be downloaded at: . References [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ,…”
unclassified
“…Notably, high powered cohort studies identify predictive miRNAs for of autism spectrum disorder [ 4 , 16 , 17 ], traumatic brain injury [ 18 , 19 , 20 , 21 ] endometriosis [ 22 ], and a variety of cancers [ 23 , 24 , 25 ]. Other recent studies include the prediction of alcohol use disorder [ 26 , 27 ], Parkinson’s Disease [ 28 , 29 ], and malignant pleural effusion [ 30 ]. Broad commonalities of these studies include saliva collection, saliva storage, miRNA extraction and isolation, and miRNA expression profiling.…”
Section: Introductionmentioning
confidence: 99%